Daily dynamics of cardiovascular system parameters in students with different chronotypes - S. I. Pavlenko; D. S. Gromova; V. A. Gvozdeva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Background. Human chronotype significantly influences the functioning of various body systems. Several genes determine chronotype. However, external factors, including social ones, also have a major influence on individual rhythm, among which work activity plays an important role. Objective of this study: to identify the characteristics of cardiovascular system parameters throughout the day in students with different chronotypes. Subject and methods. The study involved 43 students of both sexes aged 18 to 22 years. Individual circadian rhythm assessment was performed using the D. Horne – O. Östberg test modified by A.A. Putilov. Using the Korotkoff method in sitting position, systolic and diastolic blood pressure levels were recorded. Heart rate was measured at rest using a fingertip pulse oximeter "Little Doctor, MD300". Based on the recorded data, the Kerdo vegetative index was calculated to assess the leading division of the nervous system. For statistical analysis, the Shapiro-Wilk test and Wilcoxon test were used. Results. The study found that in all groups, regardless of chronotype, an increase in certain hemodynamic parameters was observed by evening. In people with morning activity type, the greatest changes throughout the day were observed in diastolic blood pressure and heart rate. In individuals with "moderate" chronotype, the most significant changes concerned systolic blood pressure parameters. In representatives of evening type ("owls"), cardiovascular system functioning parameters were most stable throughout the day. Conclusion. Despite the close relationship between chronotype and the dynamics of physiological processes, including the cardiovascular system, there are factors that can significantly influence hemodynamic parameters and nervous system tone throughout the day, one of which is work regime, its intensity and emotional component.